THE EFFECT OF AUDIO CASSETTE LEARNING MEDIA TOWARDS ENGLISH LISTENING SKILLS AT FIFTH GRADE STUDENTS OF SDN KUTA BARU 1 TANGERANG REGENCY - Ratih Ayu Wulandari; Fairus Sintawati; Ulinuha Dahlina; Peni Astuti; Meli Safira (International Journal of Education, Information Technology, and Others, 2019)
This study aims to determine the effect of audio cassette learning media towards English listening skills at fifth grade elementary school students. This research uses a quantitative approach. This study used the Quasi-Experimental Design with the Nonequivalent Control Group Design. The study population was the entire fifth grade of elementary school students, with the fifth-grade sample divided into two groups, namely the experimental class and the control class. The sampling technique was done randomly. In the data collection technique, the researcher used tests. Data analysis technique was done using T-test. The results showed that the post-test results for the experimental class was 76.67 and the control class was 61.61 and a value of 4.0. This means that there is a significant difference between the post-test results of the experimental class using audio cassette learning media and the control class using the conventional teaching method. So that, it can be concluded that there is an effect of audio cassette learning media towards English listening skills at the fifth grade students of SDN Kuta Baru 1 Tangerang Regency.